DEVELOPMENT STRATEGY OF TOURISM FLOATING MARKET LEMBANG BASED ON CORE COMPETENCE - Agus Cholik; Resista Vikaliana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Tourism Floating Market Lembang offers a different atmosphere for the visitors with interesting travel concept. The tours offered are natural attraction floating market with a wide variety of activities in it. In order to increase the number of visitors who come, Tourism Floating Market Lembang must understand its core competencies. By knowing the core competencies possessed, Tourism Floating Market Lembang , in particular the management company, can expand its tourism business venture, thereby increasing the number of visitors. Based on those reasons, this study aims to determine the core competence is owned by Tourism Floating Market and strategic formulation adaptive core competencies possessed by the object of research. A descriptive qualitative approach uses in this research. Data is collected by getting many information of Floating Market Lembang and giving an open quetionaire to six informans. One of the informans is The Marketing Manager of Floating Market Lembang (Mrs. Melani). The other informans are the visitors of Floating Market Lembang (5 informans). Data collection also collected with direct observation and documentation. This reseach took place in Floating Market Lembang, Bandung. Research time was in October until December, 2016. Data has been tested for its validity and realibility by triangulation, memberchecking and confirmability. Data analysis technique was Miles Huberman Model. Based on the research identified three core competencies. They were attractions unique concept, selection of natural and natural location and dffective marketing. Then, based on the result and discussion, identified that two business units can be formed, namely: 1.New tourism object with a unique concept 2. Culinary business